Energy scavenging using vibrations from bluetooth controlled DC motor - Ankita H Harkare; Sagar Welekar; Abhishek Maheshwari; Suraj Motwani; Saket Soholkar (Universitas Ahmad Dahlan, 2019)
Wide spectrum of research for application-based solutions has grown due to the requirement of automation of general electrical appliances. A low-cost solution is presented in this paper to control DC motor using Bluetooth module and controlled by an ARM processor. The main objective here is to build an efficient closed loop system which is wirelessly controlled by ARM processor 2103 using Bluetooth module and Bluetooth dongle. The system suggested here is expandable and can be integrated with latest technologies as well. The paper gives the details of the prototype for home automation system and gives the expected results with 0.1% tolerance. It also suggests the ways to integrate this system with the mobile phones and hence control the devices with the mobile handsets. The vibration frequency of the DC motor is used to generate electrical potential using MEMS tecnonlogy. A novel idea of self powered DC motor is thus presented by installing MEMS based energy harvester on the motor shaft.